Increased chondrocyte apoptosis is associated with progression of osteoarthritis in spontaneous guinea pig models of the disease - Zamli, Zaitunnatakhin; Adams, Michael A.; Tarlton, John F.; Sharif, Mohammed (MDPI, 2013)
Osteoarthritis (OA) is the most common joint disease characterised by degradation of articular cartilage and bone remodelling. For almost a decade chondrocyte apoptosis has been investigated as a possible mechanism of cartilage damage in OA, but its precise role in initiation and/or progression of OA remains to the determined. The aim of this study is to determine the role of chondrocyte apoptosis in spontaneous animal modelsof OA. Right tibias from six male Dunkin Hartley (DH) and Bristol Strain 2(BS2) guinea pigs were collected at 10, 16, 24 and 30 weeks of age. Fresh-frozen sections of tibial epiphysis were microscopically scored for OA, and immunostained with caspase-3 and TUNEL for apoptotic chondrocytes. The DH strain had more pronounced cartilage damage than BS2, especially at 30 weeks. At this time point, the apoptotic chondrocytes were largely confined to the deep zone of articular cartilage (AC) with a greater percentage in the medial side of DH than BS2 (DH: 5.7%, 95% CI: 4.2–7.2), BS2: 4.8%, 95% CI:3.8–5.8), p > 0.05). DH had a significant progression of chondrocyte death between 24 to 30 weeks during which time significant changes were observed in AC fibrillation, proteoglycan depletion and overall microscopic OA score. A strong correlation (p ≤ 0.01) was found between chondrocyte apoptosis and AC fibrillation (r = 0.3), cellularity (r = 0.4)and overall microscopic OA scores (r = 0.4). Overall, the rate of progression in OA and apoptosis over the study period was greater in the DH(versus BS2) and the medial AC (versus lateral). Chondrocyte apoptosis was higher at the later stage of OA development when the cartilage matrix was hypocellular and highly fibrillated, suggesting that chondrocyte apoptosis is a late event in OA.